Meningkatkan Hasil Belajar Pak dengan Model PBL Berbantuan Media Inovatif Fase C Kelas 5 SD Negeri 17 Rabak - Katarina Hendrika; Dicky Aprianto (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve student learning outcomes in Catholic Religious Education (PAK) for 5th-grade students at SD Negeri 17 Rabak through the implementation of Problem Based Learning (PBL) with innovative media. The PBL model encourages students to actively solve real-life problems, while innovative media enhances their interest and motivation to learn. Using a classroom action research (CAR) method involving 10 students, the results showed a significant improvement in learning outcomes from cycle I (71.2) to cycle II (82.8). Additionally, students' collaboration skills, critical thinking, and self-confidence also improved. The innovative media proved effective in deepening understanding and increasing student participation.